Static responses analysis of prestressing tension force effects on vertical deflection and shear force of simply-supported and continuous prestressed concrete bridges - Fadhil Naser, Ali (International Journal of Engineering and Technology, 2019)
The purpose of this study is to investigate and evaluate the effect of prestressing tension force on the static responses such as vertical deflection and vertical shear force of prestressed concrete bridges. Simply-supported I-girder bridge model and continuous box girder concrete bridge model are selected. Each model is used 12 levels of prestressing tension force ranged from 500kN to 6000kN. Finite element analysis method is used in static analysis. The results of static analysis shows that simply-supported bridge model appears the maximum value of upward deflection (18mm) due to prestressing force stage and maximum value of downward deflection (-15mm) due to service loads stage. Therefore, the prestressing tension force has significant effect to reduce the downward deflection due to service loads. This model also appears direct proportion between prestressing tension force and vertical shear force for prestressing force analysis and service loads stages. For continuous box girder bridge model, the prestressing tension force has no important effect on the upward vertical deflection due to prestressing load stage and it appears just downward vertical deflection. Therefore, this types of model needs to increase the prestressing force tension of steel tendons to reduce the downward deflection and to increases upward deflection. Continuous box girder bridge model gives opposite proportion between prestressing tension force and vertical shear force in positive and negative area within prestressing force analysis stage. Under service load stage, the positive and negative vertical shear force is decreased when the prestressing tension force increased.Â